A canção do clube da esquina como recurso pedagógico: patrimônio cultural e memória - Andrea dos Reis Estanislau Bueno (2020)
Schools and Museums are the institutions responsible for stimulating the enhancement and preservation of social memory by allowing access to our cultural and heritage assets. The aim of this work is to bring Cultural Heritage to schools, from an extension course, which aims to prepare teachers to be cultural and heritage agents, using Brazilian popular music as a didactic instrument in educational actions. Our proposal is to enable Heritage Education in the classroom from the songs of Clube da Esquina, a group of musicians from Minas Gerais led by Milton Nascimento whose trajectory blends with historical places and moments in the city of Belo Horizonte. This process aims at identifying and valuing cultural goods through affective stimulation, developing a sense of belonging and offering new learning situations, as well as strengthening ties with Heritage and contributing to the formation of cultural identity and memory. The educational resource resulting from this work is a University Extension course that promotes Heritage Education on the basis of Clube da Esquina songs.